Heterogeneity of Soft Tissue Sarcomas and Its Implications in Targeted Therapy - Du, Xin-Hui; Wei, Hua; Zhang, Peng; Yao, Wei-Tao; Cai, Qi-Qing (Frontiers in Oncology, 2020)
Soft tissue sarcomas are a set of malignancies of mesenchymal origin. Due to the rarity and similarity in clinical presentation, they are grouped together and treated similarly in clinic. The response rates for current chemotherapy are around 20% and the median overall survival for advanced soft tissue sarcoma are less than 2 years. Thus, the current strategy with identical treatment for all soft tissue sarcomas is far from satisfactory. In this study, we first reviewed the current clinical and genomic findings of soft tissue sarcoma, paying special attention to the heterogeneities among different tumors. Then we reviewed the state-of-art understanding of targeted therapy in soft tissue sarcoma. We observed tremendous heterogeneity both in clinical and genomic settings between different tumors. Individualized treatment plans demonstrated better response and disease control and should be advocated. In summary, heterogeneity of soft tissue sarcomas requires the development of individualized treatment plans such as targeted therapy.